Photorelease of glycine and beta-alanine from (7-bromocoumarin-4-yl)methyl cages - Conceição, Rafaela C. O. (2015)
The synthesis of a new 7-bromo-4-(chloromethyl)-coumarin to be used as cage for the release of bioactive molecules is presented. Ester cages of two neurotransmitter amino acids, glycine and β-alanine, were also synthetized. These neurotransmitters were chosen as models due to their biological relevance. The glycine and β-alanine ester conjugates, in methanol/HEPES buffer (80:20), were irradiated at 254, 300, 350 and 419 nm in a Rayonet RPR-100 photochemical reactor and the photolysis process was followed by HPLC with UV detection. These results were compared with those previously obtained by our research group when 4-chloromethyl-coumarin was used in the photorelease of glycine and β-alanine.